Singing crickets from Brazil (Orthoptera: Gryllidea), an illustrated checklist with access to the sounds produced - Zefa, Edison; de Pinho Martins, Luciano; Demari, Christian Peter; Acosta, Riuler Corrêa; Centeno, Elliott; Castro-Souza, Rodrigo Antônio; de Oliveira, Gabriel Lobregat; Miyoshi, Akio Ronaldo; Fianco, Marcos; Redü, Darlan Rutz; Timm, Vitor Falchi; Costa, Maria Kátia Matiotti Da; et al. (Zootaxa, 2022)
The knowledge of bioacoustics of the Neotropical crickets (Orthoptera, Gryllidea) is incipient, despite the great species diversity in the region. There are few cricket song-files deposited in the major World Sound Libraries, compared to other groups such as birds and amphibians. In order to contribute to the knowledge of the bioacoustics of Brazilian crickets, we organize, analyze and make available at Fonoteca Neotropical Jacques Vielliard (FNJV) and Orthoptera Species File (OSF) our bank of cricket songs. We deposited 876 cricket’s song files in the FNJV, belonging to 31 species and 47 sonotypes. The songs were field/lab recorded, and all individuals were collected to improve species/sonotypes taxonomic determination accuracy. We present photos (in vivo) of most recorded crickets, as well as calling song spectrograms to facilitate the species/sonotype recognition. Samples of the songs can be found online on the FNJV website, using the codes available in this work, as well as on the OSF, linked to the species name. As a result, we advance the knowledge of the songs of crickets and the current perspective of the Brazilian cricket bioacoustics. We encourage researchers to share with the public their collections of their cricket file songs both in the FNJV and the OSF.